Bacterial disinfection in a sunlight/visible-light-driven photocatalytic reactor by recyclable natural magnetic sphalerite. (January 2017) - Peng, Xingxing; Ng, Tsz Wai; Huang, Guocheng; Wang, Wanjun; An, Taicheng; Wong, Po Keung
Abstract: A 5-L reactor was designed and used to enhance the sunlight/visible-light-driven (VLD) photocatalytic disinfection efficiency towards Gram-negative bacterium ( Escherichia coli ). Natural magnetic sphalerite (NMS) was used as the photocatalyst, which could be easily recycled by applying a magnetic field. Results showed that NMS with irradiation by the blue light emitting diode (LED) lamp could completely inactivate 1.5 × 10 5 cfu/mL of E. coli within 120 min in the first three runs. However, the inactivation efficiency of E. coli started to decrease in the 4th Run, while in the 5th run, the E. coli with the initial concentration of 5 logs was inactivated to 3.3 (blue-light) and 3.5 logs (sunlight), respectively. Moreover, the stability and deactivation mechanism of NMS during subsequent runs were also studied. The results showed that the decline of the photocatalytic activity was possibly attributed to adsorption of the bacterial decomposed compounds on the active sites. In addition, photocatalytic bactericidal mechanism of the NMS in the photocatalytic system was investigated by using multiple scavengers to remove the specific reactive species. Moreover, various Gram-positive bacteria including Staphylococcus aureus, Microbacterium barkeri, and Bacillus subtilis could also be efficiently inactivated in the photocatalytic system. Graphical abstract: Highlights: Enhanced photocatalytic disinfection in a designed small-scale reactor. Recycling of natural magnetic sphalerite (NMS) by adding magnetic field. Excellent recycle usage of photocatalyst without any treatment. Good disinfection efficiency to various Gram-positive and Gram-negative bacteria.